Recommendations for facilitating offshore aquaculture: lessons from international experience - Carroza-Meza, Carlos; Fuentes, Derie; Hurtado, Carlos Felipe; Palacio, Felipe; Benetti, Daniel (Frontiers in Aquaculture, 2024)
In 2017, the Chilean government through the Chilean Economic Development Agency (CORFO) (an agency under the Ministry of Economy) launched a public call for the execution of a Technological Program to adopt, adapt, and/or developing enabling technologies for the development of Ocean Aquaculture in places with high-energy (strong waves, winds and/or currents).The consortium of companies, technology centers, and universities led by Ecosea Farming (Ecosea), focused its efforts on aspects related to structural engineering, mooring systems, sensors, Internet of Things (IoT), and other integral components, as well as essential aspects of regulation and standards. On this last topic, intensive collaborative work was carried out between the technical teams of the Andrés Bello University, the Undersecretariat of Fisheries and Aquaculture (Subpesca), the National Fisheries and Aquaculture Service (Sernapesca), and CORFO, with the aim of gathering relevant information from international experience, and establishing the main differences between aquaculture traditionally developed in the fjords, coast, estuaries, and inland sea of southern Chile and aquaculture in the high seasa practice not yet clearly defined and still indistinctly known as offshore or open ocean aquaculture. This document summarizes the main findings obtained and can be a useful guide for future experiences in other countries with important aquaculture developments.